3D in vivo imaging of the keratin filament network in the mouse stratum granulosum reveals profilaggrin-dependent regulation of keratin bundling. Issue 3 (June 2019) - Usui, Keiko; Kadono, Nanako; Furuichi, Yuki; Shiraga, Keiichiro; Saitou, Takashi; Kawasaki, Hiroshi; Toyooka, Kiminori; Tamura, Hiroomi; Kubo, Akiharu; Amagai, Masayuki; Matsui, Takeshi
Highlights: We visualized keratin filament networks in epidermal stratum granulosum in vivo . mCherry-keratin 1 labeled keratin filaments without affecting filament network. mCherry-K1 was expressed in stratum granulosum by in vivo electroporation. Filaggrin-deficient stratum granulosum exhibited reduced bundled keratin filaments.